The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/hiv.13120
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes in women living with HIV in Botswana: lower rates with dolutegravir‐ than with efavirenz‐based antiretroviral therapy

Abstract: Background There are few data on the prevalence of gestational diabetes (GDM) in pregnant women living with HIV (WLHIV) in sub‐Saharan Africa, particularly those using integrase strand transfer inhibitors such as dolutegravir (DTG). Methods We prospectively enrolled pregnant WLHIV and pregnant women without HIV ≥18 years old in Gaborone, Botswana, excluding those with pre‐existing diabetes. We screened for GDM using a 75 g oral glucose tolerance test (OGTT) performed at 24–28 weeks’ gestation or at the earlies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(39 reference statements)
1
7
1
Order By: Relevance
“…[33] However, another study found a protective effect of DTG against gestational diabetes. [34] We did not find an association between INSTI exposure and any other adverse maternal and/or pregnancy outcomes, including gestational diabetes, SGA, spontaneous abortion, stillbirth, or preterm birth. Other studies have identified an association between INSTI exposure during pregnancy and preterm birth.…”
Section: (Which Was Not Certified By Peer Review)contrasting
confidence: 64%
“…[33] However, another study found a protective effect of DTG against gestational diabetes. [34] We did not find an association between INSTI exposure and any other adverse maternal and/or pregnancy outcomes, including gestational diabetes, SGA, spontaneous abortion, stillbirth, or preterm birth. Other studies have identified an association between INSTI exposure during pregnancy and preterm birth.…”
Section: (Which Was Not Certified By Peer Review)contrasting
confidence: 64%
“…The higher prevalence of GDM in pregnant women living with HIV, however, has not been reported in studies from the United States and Botswana, where GDM prevalence was similar in women living with and without HIV. 16,17 Women in those studies had similar CD4 counts and antiretroviral therapy coverage as our cohort, but were mainly on protease or integrase inhibitor-based regimens. They also had higher BMIs and age than women in our cohort.…”
Section: Discussionmentioning
confidence: 79%
“…Women ≥35 years were most likely to develop GD in our population, which could be a proxy for age‐related weight gain [ 57 ]. A recent study in Botswana reported similar findings with GD risk increasing linearly with each year of age (aOR: 1.10, 1.04–1.17) [ 42 ]. Maternal age is also related to gravidity, which was accounted for in the modelling strategy; however, evidence from the general population indicates that the incidence of GD is three‐ to six‐fold higher among women over 40 years of age [ 58 ], and a significant proportion of women who develop GD in their first pregnancy are at greater risk of developing GD in subsequent pregnancies [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 58%
“…A comparative analysis of randomized clinical trials has shown that weight gain is greater in more recent trials with the use of newer ART regimens [ 44 ], which is consistent with post‐marketing observational studies of integrase inhibitors [ 45 ]. Preliminary studies of WLWH on integrase inhibitors during pregnancy show no cause for concern regarding gestational weight gain [ 42 , 46 ]; however, a risk prediction model based on data from South Africa suggests that treatment emergent obesity with dolutegravir‐based regimens (with tenofovir alafenamide or disoproxil and emtricitabine) for obese women (BMI ≥30 kg/m 2 ) versus those with normal BMI could increase the risk of GD four‐fold (RR: 4.31, 95% CI: 3.18–5.85) [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation